The Revolution of Arabic Syntax Learning Among Generation Z - Darmawati, Darmawati; Dalle, Ambo; Afriadi, Dedy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The revolution of Arabic syntax learning is imperative in light of generational shifts and technological advancement. This study aims to critically examine the radical transformations in Arabic syntax learning models for Generation Z, focusing on the effectiveness of applied methods. Employing a mixed-methods approach, the study combines qualitative data collected through in-depth interviews and classroom observations with quantitative data obtained via surveys and learning outcome analyses across two different timeframes. The findings reveal a significant contrast in the approach and the effectiveness of Arabic syntax instruction. Traditional learning was dominated by lecture-based and memorization methods, which, while fostering conceptual understanding, proved less effective in enhancing practical application. In contrast, for Generation Z, technology-based approaches such as interactive digital applications and gamification have increased student engagement by up to 45% compared to traditional methods. Additionally, integrating social media as a platform for syntax discussion has strengthened students' communicative competence in modern Arabic contexts. Nevertheless, the revolution in Arabic syntax learning demands a synergy between digital technology and student-centered pedagogical approaches. These findings make a significant contribution to the development of adaptive learning models aligned with the unique characteristics of Generation Z, laying the groundwork for improving Arabic language instruction in the future